A systematic review on factors affecting the likelihood of change blindness - Gibbs, Rebecca; Davies, Graham; Chou, Shihning (Taylor & Francis, 2016)
Background: The phenomenon of Change Blindness (CB) has been invoked in a number of fields of psychology, particularly eyewitness misidentification, but also hazard perception in driving behaviour. An extensive review of the existing literature suggested that there has been no systematic review to date that has investigated what factors affect CB in real-world contexts. Purpose: This article aims to systematically review factors affecting CB when measured using film or real-world paradigms. Method: Six electronic databases were searched for relevant references, alongside four E-theses. Seven experts were contacted for current and unpublished studies. Each study was compared against inclusion criteria, prior to selection and data synthesis. Results: The full search yielded 12,656 publications; 3,654 duplicates were removed and an additional 8,693 irrelevant publications were excluded. A further 295 publications were removed for not meeting the inclusion criteria. One conference abstract was excluded as contact with the authors produced no response. A total of 13 articles that met the criteria were reviewed. Conclusion: Increasing attention, the saliency of the changed object and spatial violations significantly reduce CB, specifically when measured using the real-world and film paradigms; these have implications for forensic psychology practice relevant to innocent bystanders and eyewitness misidentifications, and witnesses making positive identifications. However, a number of methodological limitations were identified which should be taken into account in designing future research.